Program Partai Persatuan Pembangunan (PPP) dalam Pembinaan Politik Masyarakat Kabupaten Deli Serdang - Hidayat, Pika Hapnijar; Arifinsyah, Arifinsyah; Sahrin, Abu (Medan Resource Center, 2025)
This study explores the political education program of the United Development Party (Partai Persatuan Pembangunan/PPP) in Deli Serdang Regency and its role in shaping the political awareness and participation of local communities. The research is driven by the question: How does PPP contribute to political socialization and civic engagement in Deli Serdang through its political outreach and organizational strategies? Employing a qualitative approach with a case study design, data were collected through in-depth interviews with PPP officials, community members, and political observers, as well as document analysis of party programs and local government reports. The findings reveal that PPP’s political programs—such as public forums, youth engagement activities, and religious-cultural events—have provided a structured platform for increasing political literacy, fostering democratic values, and promoting civic responsibility among constituents. However, the impact of these programs varies across demographic groups and is often constrained by limited resources and partisan fragmentation. The study concludes that while PPP's initiatives have contributed meaningfully to community-level political development, greater institutional support and broader participation are essential for sustained impact and inclusivity in the political process.